2020
DOI: 10.12688/f1000research.26423.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding primary ovarian insufficiency

Abstract: Primary ovarian insufficiency (POI) is an uncommon yet devastating occurrence that results from a premature depletion of the ovarian pool of primordial follicles. Our understanding of both putative and plausible mechanisms underlying POI, previously considered to be largely “idiopathic”, has been furthered over the past several years, largely due to advances in the field of genetics and through expansion of translational models for experimental research. In this review, our goal is to familiarize the multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 83 publications
(92 reference statements)
1
52
0
Order By: Relevance
“…Trisomy X (47 XXX or mosaic) (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Deletion of X chromosome (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Turner mosaic (45XO/46XX) (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Turner syndrome (Torrealday et al, 2017) Fragile X premature (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Autoimmune Chromosomal abnormalities, genetic polymorphisms, and single-gene mutations have been recognized as causes of POI (Wesevich et al, 2020). X-chromosomal defects linked to POI indicate that this chromosome is vital to normal ovarian function, as these defects cause POI development.…”
Section: Genetic Causesmentioning
confidence: 99%
See 2 more Smart Citations
“…Trisomy X (47 XXX or mosaic) (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Deletion of X chromosome (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Turner mosaic (45XO/46XX) (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Turner syndrome (Torrealday et al, 2017) Fragile X premature (Allen et al, 2007;Chapman et al, 2015;Dawood et al, 2018;Kirshenbaum and Orvieto, 2019;Wesevich et al, 2020) Autoimmune Chromosomal abnormalities, genetic polymorphisms, and single-gene mutations have been recognized as causes of POI (Wesevich et al, 2020). X-chromosomal defects linked to POI indicate that this chromosome is vital to normal ovarian function, as these defects cause POI development.…”
Section: Genetic Causesmentioning
confidence: 99%
“…Premature ovarian insufficiency (POI) is characterized by deficient ovarian sex hormones and decreased ovarian reserve, which together lead to an accelerated reduction in ovarian function and an early onset of menopause ( Wesevich et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently many studies have tested the applicability of stem cell therapies in treating infertility of ovarian aging using various stem cells including bone marrow-derived mesenchymal stem cells (BMMSCs), adipose-derived mesenchymal stem cells (ADSCS), peripheral blood mononuclear cells (PBMCs), human amniotic epithelial cells (hAECs), amniotic uid stem cells (AFSCs), umbilical cord mesenchymal stem cells (UCMSCs), menstrualblood-derived stromal cells (MenSCs),oogonial stem cells [18][19][20]. Meanwhile, many studies have demonstrated that ovarian surface epithelium (OSE)-derived ovarian stem cells (OSCs) exist in both juvenile and adult mouse ovary as well as in the postmenopausal women ovary [21][22][23][24].…”
Section: Conclusion(s)mentioning
confidence: 99%
“…Recently, many studies have examined the efficacies of stem cell therapies for treating infertility due to ovarian aging. The stem cells include bone marrow-derived mesenchymal stem cells (BMMSCs), adipose-derived mesenchymal stem cells (ADSCS), peripheral blood mononuclear cells (PBMCs), human amniotic epithelial cells (hAECs), amniotic fluid stem cells (AFSCs), umbilical cord mesenchymal stem cells (UCMSCs), menstrual blood-derived stromal cells (MenSCs), and oogonial stem cells [ 18 20 ]. Furthermore, studies have demonstrated that ovarian surface epithelium (OSE)-derived ovarian stem cells (OSCs) are present in the ovaries of juvenile and adult mice and in those of postmenopausal women [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%